Techno Resources, Transformational Leadership, Job Satisfaction And Turnover Intention - Salsa Meisita Fahrosa; Abdul Haeba Ramli; Siti Mariam; Suseno Hadi Purnomo; Dennish H. Tablante (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Techno Resources are essential to increase productivity and efficiency in organizations. However, the application of technology in the workplace often causes difficulties, which can affect Job Satisfaction and encourage employees to Turnover Intention. The purpose of this study is to investigate how Techno Resources, Transformational Leadership, Job Satisfaction, and Turnover Intention in an organization interact with each other. This study shows that Transformational Leadership is a factor that can affect how satisfied employees are with their jobs when Techno Resources affect how satisfied they are with their jobs. The results of this study are expected to provide insight for organizations on the best way to use Techno Resources and Transformational Leadership methods to increase employee productivity and retention. This study uses quantitative research using the Structural Equation Model Partial Least Square (SEM-PLS) method. Questionnaires were distributed to 150 respondents from private companies in the Tangerang area. The results of this study are expected to provide insight for organizations on the best way to use employee productivity and retention. Keywords: Techno Resources, Transformational Leadership, Job Satisfaction, Turnover Intention.